Shelf Life Of Smoked Cockatua Fish (Scarus sp) At Room Temperature - Pinamangun, Megga Ferrem; Salindeho, Netty; Taher, Nurmeilita; Dotulong, Verly; Pongoh, Jenki; Kaparang, Josefa Tety (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2023)
The research aims to determine the water content, protein content, pH, ALT, and organoleptics of parrot fish using coconut shell fumigants. The method used in this research is very exploratory research, the data is analyzed descriptively testing the data in the research data in the form of images (Histograms). The parameters used in this research are analysis of water content, protein content, pH, ALT, and organoleptics. From the research carried out, it was found that parrot fish was smoked using coconut shell fuel, and the storage time of 0 days, 2 days, and 4 days was presented in the form of a histogram and then discussed. The results of the first stage organoleptic test showed that the panelists preferred smoked parrot fish. The results of the second stage of the organoleptic test showed that the panelists preferred smoked parrot fish. The water content with the highest results is Parrotfish A1 water content 55.85%, A2 62.38% and A3 44.20%) ALT results from 0 days of storage have an average value of A1 (22 × 102 CFU/g) and 2 days have an average value of A2 (28 × 102 CFU/g) and then 4 days of storage had an average value of A3 (28 × 102 CFU/g) Smoked Parrot Fish Protein Content at 0 days of storage was 3.84. 3. The highest pH of smoked Parrot Fish was found for a storage period of 4 days, namely 7 Keywords: Parrot Fish (Scarus sp), Water Content, Protein Content, Organoleptic Abstrak Tujuan dari penelitian adalah mengetahui kadar air, kadar protein, pH, ALT, organoleptik dari ikan kakatua menggunakan bahan pengasap tempurung kelapa Metode yang digunakan dalam penelitian ini adalah Penelitian sangat eksploratif, data di analisis secara deskriptif pengujian data dalam penelitian data dalam bentuk gambar (Histogram). Parameter yang digunakan dalam penelitian ini yaitu: analisis kadar air , kadar protein, pH,ALT, dan organoleptik. Dari penelitian yang dilakukan didapatkan bahwa Ikan kakatua dengan cara pengasapan dengan menggunakan bahan bakar tempurung kelapa lama penyimpanan 0 hari , 2 hari dan 4 hari yang di peroleh di sajikan dalam bentuk Histogram kemudian di bahas. Hasil uji organoleptik tahap satu menunjukkan bahwa panelis lebih menyukai ikan kakatua asap. Hasil uji oranoleptik tahap dua menunjukkan bahwa panelis lebih menyukai ikan kakatua asap. kadar air dengan hasil tertinggi yaitu Ikan Kakatua A1 kadar air 55.85% , A2 62.38% dan A3 44.20%) hasil ALT penyimpanan 0 hari memiliki nilai rata–rata A1 ( 22 × 102 CFU/g) dan 2 hari memiliki nilai rata–rata A2 (28 × 102 CFU/g ) dan selanjutnya penyimpanan 4 hari memiliki nilai rata–rata A3 ( 28 × 102 CFU/g) Kadar Protein Ikan Kakatua asap pada penyimpanan 0 hari 3.84. 3. pH Ikan Kakatua asap tertinggi terdapat pada lama penyimpanan 4 hari yaitu 7 Kata Kunci: Ikan Kakatua (Scarus sp) , Kadar Air, Kadar Protein, pH, ALT, Organoleptik